A Karyological Investigation on Some Rare and Endangered Species of Amaryllidaceae in Turkey - Şenel, G.; Özkan, M.; Kandemir, N. (My University, 2002)
Chromosome number and morphology of three species belonging to Amaryllidaceae viz., Galanthus rizehensis Stern., Leucojum aestivum L., and Pancratium maritimum L., from the Central Black Sea Region of Turkey were analyzed. The chromosome number of P. maritimum and L. aestivum is 2n=22 while of G. rizehensis it is 2n=26.